2008
DOI: 10.1152/ajpcell.00249.2008
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-dependent regulation of the intestinal folate uptake process: studies with Caco-2 cells and native mouse intestine

Abstract: Subramanian VS, Reidling JC, Said HM. Differentiationdependent regulation of the intestinal folate uptake process: studies with Caco-2 cells and native mouse intestine. Am J Physiol Cell Physiol 295: C828 -C835, 2008. First published July 23, 2008 doi:10.1152/ajpcell.00249.2008.-Differentiation of intestinal epithelial cells is accompanied by alterations in levels of expression of many genes, including those involved in nutrient uptake. Effects of differentiation of intestinal epithelial cells on the physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
(83 reference statements)
1
20
0
Order By: Relevance
“…It has been reported that vitamin D 3 -induced gene expression increases as Caco-2 cells differentiate (Cui et al, 2009). Thus, our current findings on VDRmediated regulation of PCFT expression provide a possible molecular mechanism for a prior observation that folate uptake into Caco-2 cells is enhanced upon confluence-associated differentiation (Subramanian et al, 2008b).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…It has been reported that vitamin D 3 -induced gene expression increases as Caco-2 cells differentiate (Cui et al, 2009). Thus, our current findings on VDRmediated regulation of PCFT expression provide a possible molecular mechanism for a prior observation that folate uptake into Caco-2 cells is enhanced upon confluence-associated differentiation (Subramanian et al, 2008b).…”
Section: Discussionsupporting
confidence: 65%
“…PCFT promoter activity has been shown possibly to be epigenetically regulated by its methylation status in human tumor cell lines (Gonen et al, 2008). Furthermore, both the PCFT mRNA expression levels and PCFT promoter activity positively correlate with the level of differentiation of colon-derived Caco-2 cells (Subramanian et al, 2008b).…”
mentioning
confidence: 99%
“…Studies in mouse and rat intestines revealed higher mRNA and PCFT and RFC protein levels in the villus tip compared with expression in the crypt base (122,123). Similarly, as Caco-2 cells became confluent and differentiated, expression of both transporters increased (122).…”
Section: Vitamin Dmentioning
confidence: 99%
“…Similarly, as Caco-2 cells became confluent and differentiated, expression of both transporters increased (122). Although vitamin D 3 promotes differentiation (124,125), it is uncertain whether the increase in PCFT expression that occurs with the differentiation of Caco-2 cells, or in the villus tip versus crypt cells, is related specifically to vitamin D 3 regulation.…”
Section: Vitamin Dmentioning
confidence: 99%
“…The observed reductions in folate uptake with maturation were associated with a decrease in both the mRNA and protein abundance of RFC, possibly mediated through transcriptional mechanisms. Recently, Subramanian et al (2008) reported that the differentiation of enterocytes was associated with an upregulation in carrier-mediated folate uptake, which was associated with an increase in the abundance of mRNA and protein for both the RFC and PCFT in the intestine.…”
Section: Introductionmentioning
confidence: 99%